2015
DOI: 10.1017/s1751731115001330
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding on CO2 production and energy expenditure in ponies measured by indirect calorimetry and the 13C-bicarbonate technique

Abstract: Energy expenditure (EE) can be estimated based on respiratory gas exchange measurements, traditionally done in respiration chambers by indirect calorimetry (IC). However, the 13 C-bicarbonate technique ( 13 C-BT) might be an alternative minimal invasive method for estimation of CO 2 production and EE in the field. In this study, four Shetland ponies were used to explore the effect of feeding on CO 2 production and EE measured simultaneously by IC and 13 C-BT. The ponies were individually housed in respiration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The isotope excretion time after NaH 13 CO 3 administration is relatively fast, minutes to hours, again depending on the size of the subject. The 13 CBT has been validated against IC in many different species of animals (mouse: Speakman & Thomson, 1997; goats: Junghans et al, 1997; bulls: Junghans et al, 2007; humans: Junghans et al, 2008; mink: Larsson & Tauson, 2012; ponies: Jensen et al, 2015; Jensen et al, 2015) including dogs (Larsson et al, 2014; Larsson et al, 2014). Previous studies in dogs and ponies have suggested that measurements with the 13 CBT can be performed in a minimally invasive way by using oral administration of the isotope and collection of breath samples for isotope ratio analyses (Jensen, Larsson, et al, 2015; Larsson et al, 2015; Larsson, Jensen, et al, 2014; Larsson, Vitger, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The isotope excretion time after NaH 13 CO 3 administration is relatively fast, minutes to hours, again depending on the size of the subject. The 13 CBT has been validated against IC in many different species of animals (mouse: Speakman & Thomson, 1997; goats: Junghans et al, 1997; bulls: Junghans et al, 2007; humans: Junghans et al, 2008; mink: Larsson & Tauson, 2012; ponies: Jensen et al, 2015; Jensen et al, 2015) including dogs (Larsson et al, 2014; Larsson et al, 2014). Previous studies in dogs and ponies have suggested that measurements with the 13 CBT can be performed in a minimally invasive way by using oral administration of the isotope and collection of breath samples for isotope ratio analyses (Jensen, Larsson, et al, 2015; Larsson et al, 2015; Larsson, Jensen, et al, 2014; Larsson, Vitger, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%